2020
DOI: 10.1002/eat.23254
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance coping during mealtimes predicts higher eating disorder symptoms

Abstract: Objective: Eating disorders (EDs) are characterized by significant anxiety during mealtime that contributes to food avoidance and weight loss. Individuals with EDs commonly use avoidance coping (e.g., distraction) to tolerate meals and comply with meal plans.Although this strategy may be effective short term, a large body of anxiety literature suggests that avoidance can lead to worsening of psychological symptoms long term.Method: The current study (N = 66 individuals diagnosed with ED) used ecological moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
5
9
0
Order By: Relevance
“…Rates of being bullied, electronically bullied, and getting into physical fights were also associated with the severe DEB and suicidality class, as per prior research (Copeland et al, 2015; Klomek et al, 2007; Koutek et al, 2016), although the differential effects found among the other classes (e.g., poor self ‐ image and suicidality , weight loss and fasting , and suicidality only ) suggest distinct mechanisms in how developmental risk factors may relate to suicidality and DEB. Consistent with previous research, the associations found in this study highlight that emotion dysregulation, impulsivity, and maladaptive coping may represent common pathways linking suicidality and DEB (Goschke, 2014; Muehlenkamp et al, 2012; Pompili & Laghi, 2018; Vanzhula et al, 2020). The emergence of these overlapping behaviors and pathways indicates a strong need for interventions starting in childhood, including monitoring of core behaviors and symptoms that may escalate and persist across development (Christian et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Rates of being bullied, electronically bullied, and getting into physical fights were also associated with the severe DEB and suicidality class, as per prior research (Copeland et al, 2015; Klomek et al, 2007; Koutek et al, 2016), although the differential effects found among the other classes (e.g., poor self ‐ image and suicidality , weight loss and fasting , and suicidality only ) suggest distinct mechanisms in how developmental risk factors may relate to suicidality and DEB. Consistent with previous research, the associations found in this study highlight that emotion dysregulation, impulsivity, and maladaptive coping may represent common pathways linking suicidality and DEB (Goschke, 2014; Muehlenkamp et al, 2012; Pompili & Laghi, 2018; Vanzhula et al, 2020). The emergence of these overlapping behaviors and pathways indicates a strong need for interventions starting in childhood, including monitoring of core behaviors and symptoms that may escalate and persist across development (Christian et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The finding for adolescents that using avoidance to cope at baseline was predictive of restricting behaviour at EOT is consistent with previous research showing coping through avoidance to be a potential maintaining factor of EDs (Vanzhula et al., 2020). Individuals may avoid exposing themselves to feared situations (e.g., a calorically dense meal for fear of gaining weight), which then may strengthen this fear.…”
Section: Discussionsupporting
confidence: 90%
“…Negative affect (NA) is important in the onset and maintenance of EDs. Longitudinal studies have found that NA predicts the development of EDs, and many ED symptoms are used as coping strategies for NA (Vannucci et al, 2015; Vanzhula et al, 2020). For example, binge eating has been posited as a behavior used to escape from NA (Heatherton & Baumeister, 1991), and restrictive eating has been linked to the reduction of NA (Engel et al, 2005; Lavender et al, 2013).…”
Section: Introductionmentioning
confidence: 99%